Expanded Roles and Recommendations for Stakeholders to Successfully Reintegrate Modern Warriors and Mitigate Suicide Risk - Geraci, Joseph C.; Mobbs, Meaghan; Edwards, Emily R.; Doerries, Bryan; Armstrong, Nicholas; Porcarelli, Robert; Duffy, Elana; Loos, Colonel Michael; Kilby, Daniel; Juanamarga, Josephine; Cantor, Gilly; Sutton, Loree; et al. (Frontiers in Psychology, 2020)
This article draws upon the legends of warriors from ancient Greece and other traditions to illuminate the journey of Modern Warriors (MWs) who have served in the United States military over the last century. It then turns to stakeholders that can assist current MWs in their reintegration to civilian life and mitigate suicide risk. Until this point, without an existing and coordinated local, federal, nonprofit, and private system, rates of suicide for post-9/11 MWs after leaving the military have greatly increased, especially for young and female MWs. This is due in part to the military satisfying many of MWs’ needs by providing units, leaders, and a mission during the Departure and Initiation stages of the MW journey. However, as MWs exit the military and face the difficult task of reintegration, the absence of units, leaders, and mission leads to deteriorating psychological health and increasing suicide risk. Written primarily by post-9/11 MWs, this article proposes recommendations for stakeholders to better reintegrate MWs and mitigate suicide risk. The authors strive to develop a system that satisfies MWs’ reintegration needs and enables MWs to be well positioned to continue their next ‘mission’ - to serve and improve society.